SNAKES AND LADDERS GAME MEDIA DEVELOPMENT FOR GEOGRAPHY LEARNING - Ika Listiqowati; Waldayanti M Umar; Iwan Alim Saputra; Suwarni Suwarni; I Putu Raditya Eka (GeoEco, 2025)
This research addresses many students' common challenges: difficulty understanding learning material, lack of motivation, passivity in class, and suboptimal learning outcomes. To tackle these issues, the researchers This research employed the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The research participants comprised 34 students from class XIA at SMAN 2 Palu. Data collection techniques included tests, questionnaires, and observations. The Snakes and Ladders game underwent rigorous validation at several levels:  validity of the material covered, resulting in a 100% score (very high category). The game design and components were evaluated by media specialists, receiving a perfect 100% score, indicating a very high quality of the physical product. Education practitioners assessed the game's feasibility and value in real classroom settings, giving it a 97.91% rating (very high category). Furthermore, a trial with a small student group demonstrated remarkable improvements in academic performance. The average normalized learning gain (N-gain) was 0.71, falling into the "very high" category. This means the game was highly effective in helping students learn and retain geographical concepts. In summary, this meticulously designed educational game was valid (as judged by experts) and practical (as shown by student outcomes). It has the potential to make geography education much more engaging and fruitful. The researchers suggest future studies explore the Snakes and Ladders game development format to teach different subjects or topics.